(3OjhGf GeQF GdbjSs - (3GeQD GdbjS Hf MLQ Hf GdMGQK GdcfOj, ef Hfj Bcd GdeQGQ , J (B80 (3b g`s
(3ChdgG (B:s
(3abdJ dgG SjQi hCQNj ReGeg hdG JHYOjfG ef LfGc GdeYdd s
(3BNQgG (B:s
(3adeG CLf GdTeS Yfj VjGDgG fRdJ Edjg bGFekG HGdMVjV s
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B351s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B32 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B776s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3GdJGQjNs